Role of growth hormone signaling pathways in the development of atherosclerosis. (August 2020) - Ishikawa, Mayumi; Toyomura, Junko; Yagi, Takashi; Kuboki, Koji; Morita, Toshisuke; Sugihara, Hitoshi; Hirose, Takahisa; Minami, Shiro; Yoshino, Gen
Abstract: Objective: The direct actions of growth hormone (GH) in the development of atherosclerosis are unclear. The goal of this study was to characterize GH-induced changes in expression of signaling pathway elements and other proteins that may be related to atherosclerosis. Methods: Human umbilical vein endothelial cells (HUVEC) and THP-1, a human acute monocytic leukemia cell line, were stimulated by exposure to 10 −9  M or 10 −8  M human GH with or without pretreatment with a mitogen-activated protein kinase kinase (MEK) 1 inhibitor. Levels of transcripts encoding vascular cell adhesion molecule (VCAM) -1, E-selectin, monocyte chemotactic protein (MCP-1), interleukin (IL) -6, and IL-8 were investigated by reverse transcription (RT) -PCR. For the quantitative adhesion assay, THP-1 cells or human primary monocytes were fluorescently labeled with 3'- O -acetyl-2′, 7′-bis(carboxyethyl) -4 diacetoxymethyl ester (BCECF/AM). HUVEC treated with human GH were co-incubated with BCECF-labeled THP-1 cells. One hour later, the number of BCECF-labeled THP-1 cells was assessed. An equivalent experiment was performed using BCECF-labeled primary monocytes, and the number of monocytes adhering to HUVEC was counted. Results: Treatment with hGH increased the levels of E-selectin - and VCAM-1 -encoding mRNAs in HUVEC. This effect was attenuated by pretreatment with a MEK1 inhibitor. Furthermore, hGH treatment increased adhesion of BCECF-labeled THP-1 cells or primary monocytes to HUVEC, and this effect was attenuated by pretreatment with a MEK1 inhibitor. Conclusions: VCAM-1 and E-selectin expression was stimulated by GH via the mitogen-activated protein kinase pathway, resulting in augmented adhesion of THP-1 cells and monocytes to HUVEC. These data suggested that GH directly stimulates the development of atherosclerosis. Highlights: GH increased mRNA expressions of VCAM-1 and E-selectin on HUVEC. The GH effects were suppressed by MEK-1 inhibitor, but not by JAK2 inhibitor. GH increased THP-1, which is human acute monocytic leukemia cell line, attachment to HUVEC. The attachment was suppressed by MEK1 inhibitor. These data suggest that GH stimulates development of atherosclerosis via srk-erk pathway without IGF-I.